The knowledge solution. - Attwood, Bain (Melbourne University Press, 2019)
What can we learn from recurring events across the recent history of Australia, of colonisation, nationalism, racism, fighting on foreign shores, land booms, industrial campaigns and culture wars? Arguments about the discipline of Australian History, from thinkers across the ideological and historical spectrum, are distilled in these extracts and essays.